FRI0605-HPR MORTALITY AND SURVIVAL IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS IN ARGENTINA. A MULTICENTER STUDY ON BEHALF GESAR-LES. (2nd June 2020) - Bertolaccini, M. C.; Soria Curi, Y.; Gonzalez Lucero, L.; Espasa, G. V.; Barbaglia, A. L.; Sueldo, H. R.; Leguizamón, M. L.; Mazza, S. M.; Santana, M.; Galindo, L. M.; Águila Maldonado, R.; García, M.; et al.
Abstract : Background: The mortality rate in patients with systemic lupus erythematosus (SLE) is 2–3 times higher than in the general population. However, survival in these patients has improved significantly and is currently 95% at 5 years according to different studies. Since the last 20 years, there are no new reports on this issue in Argentina. Objectives: To analyze the factors associated with mortality, survival and causes of death in patients with SLE. Methods: Longitudinal - multicenter study, in which 10 rheumatology centers of Argentina participated. Patients with SLE (ACR 1997 and / or SLICC 2012 criteria) with a minimum follow-up of 6 months monitored between January 2008 and December 2018 were included. Demographic, clinical, laboratory, therapeutic variables (treatments received during the evolution of the disease and within 60 days prior to death or last control); mortality, causes of death and survival at 5, 10 and 20 years were evaluated. Statistical analysis: descriptive statistics, Kaplan-Meier survival curves and Cox regression model. Results: Three hundred and eighty two patients were included; 90% women and 82% mestizos. The mean of evolution time of SLE was 4.1 ± 6.7 years. The mean age at the last control or death was 37.2 ± 12.7 years, SLEDAI 3.2 ± 4.2 and SLICC 1.2 ± 1.9. Mortality was 12% (95% CI [8-15]) and the causes of death were: Infections (27), cardiovascular disease (6), SLE activity (3), catastrophic antiphospholipid syndrome (2) and other causes (8). Using the variables associated with mortality in different Cox regression models, the variables that increased the risk of death significantly were: renal involvement (RR 3.3), cardiac involvement (RR 2.7), central nervous system involvement (RR 2.1), arterial thrombosis (RR 2.3), hyperlipemia (RR 2.4), number of infections (RR 1.2) and last SLEDAI (1.1). The time of HCQ use greater than 36 months decreased the risk of death in this cohort by 40% (p 0.03). Prednisone (maximum dose and time) was not associated with mortality (p NS). When analyzing the last treatment and adjusting it for final SLEDAI, HCQ was a mortality protection factor (RR 0.4) while the use of cyclophosphamide alone or associated with prednisone was a risk factor for death (RR 5.2). Significant differences were found when analyzing the causes of death according to the SLE evolution time (p 0.017): patients who died from infection had less evolution time (Me 2.25 years), than those who died due to cardiovascular causes (Me 10 years) or SLE activity (Me 15 years). In this cohort of patients, survival was 93% at 5 years, 88% at 10 years and 72% at 20 years. Conclusion: Mortality in this series of patients was 12% and infection was the leading cause of death. The use of HCQ for a period greater than 36 months, decreased the risk of death 40%. Disclosure of Interests: None declared